A historical Greek reader - Stephen Colvin (Oxford University Press, 2007)
A Historical Greek Reader provides an introduction to the history of the ancient Greek language by means of a series of texts with linguistic commentary, cross-referenced to each other and to a reference grammar at the front. It offers a selection of epigraphic and literary texts from the Mycenaean period (roughly the fourteenth century BC) to the koiné (the latest text dates to the second century AD), and includes a wide range of Greek dialect texts. The epigraphic section balances a number of well-known inscriptions with recent discoveries that may not be easily available elsewhere; a selection of literary texts traces major developments in the language of Greek poetry and literary prose. The book finishes with an account of the linguistic and sociolinguistic background of koiné Greek. The commentary assumes no prior knowledge of Greek historical linguistics, but provides a basic amount of up-to-date bibliography so that advanced students and others can pursue linguistic issues at greater depth where necessary